Avaliação de inteligibilidade, compreensibilidade e grau de sotaque estrangeiro do inglês-l2 de alunos brasileiros do 6o e 9º anos do ensino fundamental em sistema bilíngue de ensino - Mendes, Matheus Lima (2024)
The influence of the English language on the international scene is undeniable. From commercial exchanges to the choice of movies at the cinema, the English language is, and has been for a long time, translated into our culture, economy, tourism, entertainment and more. The classroom is one of the spaces where English has an influence. Underpinned by the law, the teaching of this foreign language takes on different forms and uses different technologies to achieve the main objective, creating a community of speakers. Bilingual educational projects, a type of bilingual education, have emerged in this movement with the aim of training students as global and integral citizens, integrating the teaching of a language into the mother tongue curriculum. In this study, we sought to ascertain how learners belonging to these projects manage to perform oral activities in English. The aim of this study was to assess the oral English language dimensions of two groups of elementary school students in the final years (6th and 9th grades) of a bilingual project located in the city of Fortaleza. The dimensions are intelligibility, comprehensibility and accentedness. The operationalization of these theoretical constructs was validated based on the definitions proposed by Munro and Derwig (1995). The methodology used was qualitative and quantitative. A group of seventeen students were selected to take part in the research: 8 sixth graders and 9 ninth graders. Two semi-spontaneous production tasks were carried out: a) reading isolated words; b) describing a picture. In addition, the students answered questions about their learning history. The audios were listened to and judged by a panel of judges made up of four native English speakers. The panel of judges also filled in a form with information about how long they had lived in their country and had lived with Brazilians. The quantitative results showed that 9th graders reached a higher intelligibility threshold than 6th graders for both tasks; the degree of difficulty (comprehensibility) was not directly correlated to the grade effect; and the degree of foreign accent was higher for 6th graders. Qualitatively, in another area of the results section, the most common deviations from different natures found in both tasks in addition to pronunciation were the use of prepositions and syntactic constructions. On the pronunciation of certain phonemes, the sounds prove to be challenging.